The Influence of Compensation, Work Environment, and Workload on Turnover Intention Phenomena at Royal Orchid Garden Hotel - Sahala Manalu; Felik Sad Windu Wisnu Broto; Ameilia Magdalena Kristiyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Turnover intention refers to the employee's voluntary or involuntary intention to leave the job. There are several variables that influence the level of intention to leave: compensation, work environment, and workload. The purpose of this study is to determine how compensation, work environment, and workload influence retirement intentions at the Royal Orchid Garden Hotel. The population and sample for this study are employees of the Royal Orchid Garden Hotel, and the sampling method used is nonprobability sampling. The number of study samples is 38, and data are collected by distributing questionnaires. A data analysis technique using multiple regression As a result, it was found that compensation, work environment, and workload all affected turnover intention. Work environment has a positive and significant impact on turnover intentions, whereas compensation and workload have a negative impact on turnover intentions.